¿Vuelve el fascismo? "El fascismo que viene", de Jacques Julliard. Madrid, Ed. Acento, 1994. 170 págs. - Hubeñak, Florencio (1997)
Fil: Hubeñak, Florencio. Pontificia Universidad Católica Argentina; Argentina